Students priming students for success: Students as partners in development of pre-lecture resources for introductory genetics - Balakumar, Paary; Fice, Heather; Richer, Samuel; Western, Tamara; Yao, Jacqueline (International Journal for Students as Partners, 2024)
Introductory science courses can be a struggle for instructors and students not only because of the challenging nature of the material, but also due to differences in the background knowledge of students. Provision of pre-lecture resources reviewing or introducing key concepts is recommended to support diverse students. In this paper, we describe the iterative design, implementation, and assessment of pre-lecture PRIMERs in a large, introductory genetics course. The development of PRIMERs was conceived, driven, and performed by a student-staff team. Data over 2 years demonstrate that most students considered that PRIMERs supported their learning of the lecture material. Student comments revealed that they found the summaries and practice problems useful, and that they used PRIMERs both as lecture preparation and examination review resources. These results suggest that the students-as-partners model is an effective way to create and refine course resources.